The Power of Binge-Watching on Continuation Intention of Video on Demand Mediated by Fear of Missing Out in the Young Generation - Fauzi, Firman; Hudaya, Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
The evolving impact of binge-watching influences consumers' intentions to continue using video-on-demand (VOD) platforms, with fear of missing out as a mediating factor. This study focuses on young individuals aged 17-25 years. Employing a quantitative research design, it aims to demonstrate the cause-and-effect relationships between binge-watching and continuation intention, mediated by fear of missing out. The novelty of this research lies in exploring both the direct relationship between binge-watching and continuation intention and the mediating role of fear of missing out, offering deeper insights into the underlying mechanisms of consumer behavior. Data analysis was conducted using the Smart PLS application, utilizing primary data for the study. The findings reveal that fear of missing out directly have a positive and significant impact on the continuation intention using video-on-demand services. While fear of missing out also positively influences binge-watching but this effect is not significant. Additionally, binge watching exerts a positive and significant effect on the continuation intention for video-on-demand. However, indirectly, binge watching has a positive but not significant effect on the continuation intention for video-on-demand when mediated by fear of missing out